SECURITY STRATEGY IN FACING PHISHING AND SKIMMING THREATS: ANALYSIS AND TECHNOLOGY SOLUTIONS AT BANK MUAMALAT INDONESIA DENPASAR BRANCH OFFICE - Kurniawati, Kurniawati (widya balina, 2025)
Abstract. The background to this research is that the trend of non-cash or cashless transactions is increasingly widespread in Indonesia. The Bank is also trying to expand its network sector by providing a number of conveniences when carrying out financial transactions without the need to come to the bank. One of them is transactions via smartphone or M-Banking. However, behind the development of banking and the ease of making transactions via M- Banking, there is also the risk of cyber-based crime or threats, so this research aims to analyze the security of transactions when using M-Banking services. The focus of this research is: 1) What is the security of transactions when using M-Banking services at Bank Muamalat Indonesia Denpasar Branch Office? 2.) What are the efforts to increase security for customers who make transactions via M-Banking services at Bank Muamalat Indonesia Denpasar Branch Office? The objectives of this research are: 1) To find out the security of transactions when using M-Banking services at Bank Muamalat Indonesia Denpasar Branch Office. 2) To find out how efforts to increase transaction security are carried out by Bank Muamalat Indonesia Denpasar Branch Office. The research method that will be used is descriptive qualitative, with data collection techniques through observation, interviews and documentation, as well as data validity techniques through the triangulation method. The research results will be presented in a descriptive manner. The result of this research is that transaction security in M-Banking services carries out risk analysis to detect threats that occur. 1) risks in using M-Banking services can be detected through the risk analysis process carried out by the bank, which includes identification, evaluation and risk assessment, as well as risk management. 2) the improvement efforts made are by managing customer information security in accordance with CIA standards (Confidentiality, Integrity, Availability) so that customers can use M-Banking services safely and comfortably.